2022
DOI: 10.15258/sst.2022.50.1.06
|View full text |Cite
|
Sign up to set email alerts
|

Single count of radicle emergence and mean germination time estimate seed vigour of Chinese milk vetch (Astragalus sinicus)

Abstract: This research explored the relationship between a single count of radicle emergence (RE) and mean germination time (MGT) with seed vigour for Chinese milk vetch (Astragalus sinicus) (CMV), a globally important legume used as a forage, green manure, and rotation crop. Fourteen seed lots of CMV were used to determine standard germination (SG), RE and MGT in the laboratory. Field experiments were conducted at two sites to measure the emergence performance including field emergence (FE), seedling dry weight (SDW) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…All seed lots used in the present experiment were from a single cultivar; thus, any differences in their germination and emergence patterns and stress tolerance were not due to their genotypes. Therefore, from a seed physiology perspective, the difference in the above traits between seed lots was most likely due to different vigor levels caused by seed aging and deterioration [18]. From the start of seed imbibition to germination or emergence, metabolic repair, including DNA repair, is required and is a necessary step for the subsequent events leading to germination and emergence [55].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All seed lots used in the present experiment were from a single cultivar; thus, any differences in their germination and emergence patterns and stress tolerance were not due to their genotypes. Therefore, from a seed physiology perspective, the difference in the above traits between seed lots was most likely due to different vigor levels caused by seed aging and deterioration [18]. From the start of seed imbibition to germination or emergence, metabolic repair, including DNA repair, is required and is a necessary step for the subsequent events leading to germination and emergence [55].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has suggested the presence of a positive linear relationship between seed vigor and seedling emergence in the field [16,17]. Tao et al found that there was an advantage in using high-vigor CMV seeds to achieve better seedling emergence, whereas low-vigor seeds caused limited seedling emergence [18]. The selection of high-vigor seeds has also been proven to be helpful for seedling emergence in other forage legumes, such as alfalfa (Medicago sativa L.) [19], white clover (Trifolium repens L.) [20], and birdsfoot trefoil (Lotus corniculatus L.) [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seed vigor testing is an important component of quality assurance in crop and forage seed production [23,24]. The traditional standard germination (SG) test, conducted according to the International Seed Testing Association, is generally used to evaluate seed quality [25].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the mean germination time (MGT) of pant seed lots determined during RE test in the laboratory was found to be related to FE [39,40]. In low-vigor seeds, the RE is delayed, and evidence has indicated that the vigor level determines the length of this delay, which has been referred to as the lag period and described by the MGT [24]. Thus, the test based on the measurement of MGT also has great potential as an efficient way to test seed vigor [15].…”
Section: Introductionmentioning
confidence: 99%